Economic and Statistical Analysis of the Management Efficiency by the Supply Chain Strategy and Grouping Method - Ekaterina Anatolevna Grigoreva; Elvira Anasovna Polovkina; Liliya Faridovna Zulfakarova (International Journal of Supply Chain Management, 2019)
The paper considers the possibility of using statistical methods to identify the impact of organizational factors on improving production efficiency. It investigates the existing problems in the application of the grouping method in the analysis of management effectiveness. The authors used a systematic approach to the statistical study of production and management efficiency. Methodological approaches to the integrated assessment of enterprise activities were developed by combining three characteristics in one grouping – the level of technical equipment, labor efficiency and capital productivity. Further research is aimed at developing and examining a generalized assessment of the organizational and technical level of enterprises on the basis of the grouping method.